Towards Just Institutional Approaches to Conflict Prevention and Resolution - Rianka Rijnhout (Utrecht Law Review)
In all societies around the world, conflicts arise. Some may be smaller conflicts between individuals and others larger ones between communities. It might be possible to prevent some conflicts from escalating, but, in all cases, conflicts will need to be resolved in order for those involved to be repaired and move forward productively. Individuals have the right to access justice and victims the right to remedies, yet realising these rights in practice is far from straightforward and subject to legal innovations. These issues and more were examined at the 2023 conference entitled: ‘Towards just institutional approaches to conflict prevention and resolution’, organised by the Universities of Utrecht, Nijmegen, and Leiden in the partnership ‘Institutions for Conflict Resolution’.1 This special issue of the Utrecht Law Review is one of the results of that conference.